Development of material contents and online assessment based on the SEVIMA EdLink platform for online learning of program evaluation subject during Covid-19 pandemic in Indonesia - Dewa Gede Hendra Divayana; Agus Adiarta; P. Wayan Arta Suyasa (Journal of Technology and Science Education, 2021)
One of the free platforms made by IT companies in the education sector in Indonesia can be used to facilitate online learning at home during the Covid-19 pandemic. The platform is called the SEVIMA EdLink. This platform needs to be known by academics and the wider community of education in the world. This platform provides facilities to make it easier for users to input material content and online assessment forms. The purpose of this research was to demonstrate the development of material contents of the ‘Program Evaluation’ subject and its assessment form that was embedded into the SEVIMA EdLink platform. The approach used in this research was a development based on the 4D model (Define, Design, Develop, and Disseminate). Subjects who were involved in testing the material contents were 29 students. The measuring instruments used in testing the material contents were questionnaires. Subjects who were involved in the content validity test for multiple-choice test questions were six experts, and two experts were involved in the content validity test for essay test questions. The tools used in testing the content validity of multiple-choice test questions or essay test questions were checklist documents. The analysis technique of the test results of the material contents was descriptive quantitative. The analysis technique for multiple-choice test questions and essay test questions was the comparison of content validity test results with the standard scores of content validity based on Guilford. This research results showed the quality percentage of material contents in the subject of ‘Program Evaluation’ was a good category. The content validity results of the multiple-choice test questions and essay test questions were both in the excellent category.